Proposal for Prevention of Occupational Disease Risk Using the Hiradc Method at PT X in the Dyeing Department - David Anjaya, Christian; Sukapto, Paulus (Ann Publisher, 2024)
People in this era have various needs in carrying out life. The needs that need to be used by the community have multiple kinds of things, such as clothing. Clothes used by the community go through various processes before becoming finished goods. Before becoming ready-to-wear, clothes came from raw materials such as fabric rolls. There are multiple production processes, such as yarn, fabric, chemical dyeing, etc. One of the places where fabrics are produced is textile factories. A textile factory is a company that produces products in the form of fabrics. The manufacture of fabrics that occur in textile factories must involve mixing chemicals so that the fabric has good quality. The process of mixing these chemical substances involves workers, and the chemical substances used are classified as Hazardous and Toxic Materials (B3), so these chemicals can have a bad impact on their workers if there is physical contact with the worker's body. Exposure to chemicals in the worker's body will cause a risk of developing Occupational Diseases (PAK). Therefore, in this study, data will be processed to prevent workers' risk of Occupational Diseases (PAK) using the HIRADC (Hazard Identification, Risk Assessment, and Determining Control) method. The proposal given in this study is a proposal for the use of Personal Protective Equipment (PPE) and Standard Operating Procedure (SOP) for preventive measures against Occupational Diseases (PAK) for workers